2017
DOI: 10.1111/jmi.12580
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans biofilms: comparative analysis of room‐temperature and cryofixation for scanning electron microscopy

Abstract: Biofilms are frequently related to invasive fungal infections and are reported to be more resistant to antifungal drugs than planktonic cells. The structural complexity of the biofilm as well as the presence of a polymeric extracellular matrix (ECM) is thought to be associated with this resistant behavior. Scanning electron microscopy (SEM) after room temperature glutaraldehyde-based fixation, have been used to study fungal biofilm structure and drug susceptibility but they usually fail to preserve the ECM and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
(67 reference statements)
1
2
0
Order By: Relevance
“…In particular, two types of peculiar extracellular matrix (ECM) architecture could be observed: (i) an extremely thin “blanket-like” layer covering the areas between hyphae (Figure 1B); (ii) very fine “mesh-like” layer wrapping the filaments of hyphae (Figure 1C). The biofilm morphology of high resolution and magnification was investigated and imaged by SEM technique to confirm the biofilm-formation in this study and the SEM images obtained are similar to those reported previously (Brilhante et al, 2017; Vila et al, 2017; Guzel Tunccan et al, 2018).…”
Section: Resultssupporting
confidence: 81%
“…In particular, two types of peculiar extracellular matrix (ECM) architecture could be observed: (i) an extremely thin “blanket-like” layer covering the areas between hyphae (Figure 1B); (ii) very fine “mesh-like” layer wrapping the filaments of hyphae (Figure 1C). The biofilm morphology of high resolution and magnification was investigated and imaged by SEM technique to confirm the biofilm-formation in this study and the SEM images obtained are similar to those reported previously (Brilhante et al, 2017; Vila et al, 2017; Guzel Tunccan et al, 2018).…”
Section: Resultssupporting
confidence: 81%
“…These biofilms are major virulence factor and play an important role in C. albicans pathogenesis. The structural complexity and polymeric extracellular matrix make biofilms more resistant to antifungal drugs than planktonic cells [64,65]. It has been reported that C. albicans can form biofilms on almost any kind of medical device such as vascular and urinary catheters, joint prostheses, cardiac valves, artificial vascular bypass devices, pacemakers, ventricular assist devices and central nervous system shunts [66].…”
Section: Discussionmentioning
confidence: 99%
“…However, we observe few pseudohyphae. Regarding the biofilms of this study compared with those of past reports, we should note that the biofilms in this study formed very large masses with dense ECM, and they seemed quite sticky [ 12 , 21 , 22 , 23 ]. We theorized that C. parapsilosis in invasive fungal infections likely forms unusual biofilms with very dense ECM.…”
Section: Discussionmentioning
confidence: 50%